Teaching persuasive essay writing online to first-year undergraduates: A phenomenological study of instructional design and learning experiences - Abdul Karim; Md Abdullah Al Mamun; Shahin Sultana; Muhammad Kamarul Kabilan (PLoS ONE, 2026)
The teaching and learning of academic essays faced difficulties in in-person classes. Challenges in academic essay instruction were exacerbated in online learning environments during COVID-19. Yet some institutions arranged sophisticated platforms to share instructional materials for imparting English language education online. The focal university was one such progressive institution. Like other courses, English language education was delivered through ‘Arwa’, an online platform developed by the university to support teaching and learning during the pandemic. The phenomenological study aimed to understand how instructional materials designed for an English foundation course contributed to first-year undergraduates’ experiences of learning persuasive essay writing. Data were collected primarily through semi-structured interviews and supplemented by an open-ended questionnaire administered to the same eight participants. Phenomenological thematic analysis was applied to interpret the data. The findings reveal how participants experienced the instructional design and materials as supporting their engagement with outlining, drafting, editing, and revising persuasive essays. Participants also described collaborative writing and rubric-guided peer feedback as meaningful learning experiences that supported their engagement with persuasive essay writing. From a phenomenological perspective, the study contributes to understanding how learners make sense of persuasive essay writing through structured online instruction, collaborative writing, and rubric-guided peer feedback. Pedagogically, the findings highlight the value of sequenced instructional materials, collaborative writing, and guided peer interaction in supporting students’ engagement with persuasive writing in online and blended learning environments.